The Impact of Procedural Justice and Trust on Customers' Continuity Intention Toward Healthcare Providers - Changjoon Lee PhD; Soohyo Kim PhD; Young-Kyou Ha PhD (SAGE Publishing, 2024)
As life has become noticeably more comfortable compared to the past, there is a mounting interest in various service sectors, such as healthcare, where growing demand has led to an increase in the number facilities that supply products essential to service provision. Enhancing the service quality is critical to gaining an advantage in the fiercely competitive healthcare environment and is especially important as the outcomes encompass not only the treatment of disease but also patients' emotional and experiential satisfaction. This study presents procedural justice and two dimensions of trust as factors related to physician and patient relationship, investigating their effects on patients' intention to continue the relationship with their healthcare providers. We found that procedural justice had a positive effect on the two dimensions of trust, and the latter had a significant positive effect on the continuity intention. As this study verifies the necessity of procedural justice and trust for patients to continuously experience medical services, it is imperative for the healthcare industry to understand and incorporate these factors into their practices.